2020
DOI: 10.4103/njcp.njcp_134_19
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of pretreatment thrombocytosis in epithelial ovarian cancer

Abstract: Aims: This study was aimed at investigating the prognostic impact of pretreatment thrombocytosis in epithelial ovarian cancer (EOC) patients in Lagos, Nigeria. Methods: This was a retrospective cohort study involving the review of the clinical record of 72 patients with histologically confirmed EOC who were managed at the Lagos University Teaching Hospital, Lagos, Nigeria over a 7-year period from January 2010 to December 2016. Information on the sociodemographic data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Many recent studies have also shown that certain hematologic markers, can be used to identify individuals with a high risk of death from some tumors 27 , 28 , 29 including EOC. 11 , 30 The measurement of preoperative hematological markers is cheap, noninvasive, and relatively easy compared to using genetic molecular biomarkers. 30 Mortality was found to be associated with pretreatment platelet, hemoglobin, and white blood cell levels in our univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many recent studies have also shown that certain hematologic markers, can be used to identify individuals with a high risk of death from some tumors 27 , 28 , 29 including EOC. 11 , 30 The measurement of preoperative hematological markers is cheap, noninvasive, and relatively easy compared to using genetic molecular biomarkers. 30 Mortality was found to be associated with pretreatment platelet, hemoglobin, and white blood cell levels in our univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, following adjustments in the final multivariate analyses, none of these hematological markers could independently predict early mortality risk in EOC patients and these findings confirmed that these markers could be surrogates for other prognostic indicators, such as advanced‑stage disease, suboptimal cytoreduction, or even medical comorbidity. 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations